The association of stem cell factor and soluble c-Kit (s-cKit) receptor serum concentrations with the severity and risk prediction of autism spectrum disorders - Mashayekhi, Farhad; Shabani, Somayeh; Sasani, Soheila Talesh; Salehi, Zivar (Metabolic brain disease, 2022)
S tem cell factor (SCF) and its receptor (c-kit) signaling play important role in normal brain physiology including neurogenesis, synapse formation and spatial learning function of the hippocampal region of the brain. Autism spectrum disorder (ASD) is believed to result from abnormal development of neuronal networks and synaptic function. The aim of this study was to evaluate the SCF and its soluble receptor (s-ckit) serum concentrations in ASD. We also studied the serum SCF and s-ckit concentration with the severity of ASD (Levels 1-3; Mild, Moderate and severe, respectively). Ninety five patients with ASD (Mild; n=33, Moderate; n=32 and severe; n=30) and 82 normal controls age matched were included in this study. The serum concentration of SCF and s-ckit were measured by enzyme-linked immunosorbent assay (ELISA). The SCF serum concentration in control subjects was 3.45±1.06 ng/ml and in ASD was 3.41±0.92 ng/ml (P=0.88). The serum levels of s-ckit in control and ASD groups were 56.82±13.22 ng/ml and 67.11±12.00, respectively (P=001). We have also studied serum SCF and s-ckit concentrations with the severity of ASD. The serum concentration of SCF in mild, moderate and severe ASD groups was 3.45±0.93, 3.4±0.87 and 3.43±0.98 ng/ml, respectively (P>0.05) and for s-ckit was 48.77±9.28, 61.66±12.18 and 93.11±14.81ng/ml, respectively (P<0.05). The result of this study suggests that serum s-cKit concentrations may provide a reliable and practical indicator of ASD and positively correlated with disease severity. It is also concluded that s-cKit might be involved in the pathophysiology of ASD.